Desire, practical reason, and the good classical and contemporary perspectives - Tenenbaum, Sergio, 1964- (New York ; Oxford : Oxford University Press, 2010)
Philosophers disagree sharply over how we are supposed to understand the notions of 'desire' and 'good', how these notions relate, and whether both play a significant and independent role in practical reason. This volume brings together 'systematic' and more historically-oriented work on these issues.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Good and evil; Practical reason; Desire (Philosophy)